Deepure Tea Improves High Fat Diet-Induced Insulin Resistance and Nonalcoholic Fatty Liver Disease - Deng, Jing-Na (Evid Based Complement Alternat Med, 2015)
This study was to explore the protective effects of Deepure tea against insulin resistance and hepatic steatosis and elucidate the potential underlying molecular mechanisms. C57BL/6 mice were fed with a high fat diet (HFD) for 8 weeks to induce the metabolic syndrome. In the Deepure tea group, HFD mice were administrated with Deepure tea at 160 mg/kg/day by gavage for 14 days. The mice in HFD group received water in the same way over the same period. The age-matched C57BL/6 mice fed with standard chow were used as normal control. Compared to the mice in HFD group, mice that received Deepure tea showed significantly reduced plasma insulin and improved insulin sensitivity. Deepure tea increased the expression of insulin receptor substrate 2 (IRS-2), which plays an important role in hepatic insulin signaling pathway. Deepure tea also led to a decrease in hepatic fatty acid synthesis and lipid accumulation, which were mediated by the downregulation of sterol regulatory element binding protein 1c (SREBP-1c), fatty acid synthesis (FAS), and acetyl-CoA carboxylase (ACC) proteins that are involved in liver lipogenesis. These results suggest that Deepure tea may be effective for protecting against insulin resistance and hepatic steatosis via modulating IRS-2 and downstream signaling SREBP-1c, FAS, and ACC.